2013
DOI: 10.1016/j.humpath.2012.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new histologic staging and grading system for primary biliary cirrhosis in comparison with classical systems

Abstract: Recently, our research team proposed a new histological staging and grading system for primary biliary cirrhosis (PBC) that takes into account necroinflammatory activity and histological heterogeneity. The present study aimed to confirm the usefulness of the new evaluating system. A total of 152 liver biopsy specimens and clinical data (including outcomes in patients with PBC before treatment with ursodeoxycholic acid) were analyzed with respect to the new system. Staging was evaluated on the basis of 3 histol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 18 publications
(10 reference statements)
6
47
0
2
Order By: Relevance
“…showed a significant prognostic value of Nakanuma components fibrosis and CBP deposition, as well as Nakanuma and Ludwig staging systems as a whole for the development of cirrhosis related conditions before ursodeoxycholic acid (UDCA) treatment. [24] In a retrospective cohort of 58 PBC patients Chan et al confirmed the Nakanuma system as a prognostic factor for liver related events, while the Ludwig system was not. [27] It must be stated that, despite that PSC and PBC are both cholangiopathies, sharing biochemical, clinical and a some morphological features, considerable differences exist in both disease entities [15].…”
Section: Discussionmentioning
confidence: 98%
“…showed a significant prognostic value of Nakanuma components fibrosis and CBP deposition, as well as Nakanuma and Ludwig staging systems as a whole for the development of cirrhosis related conditions before ursodeoxycholic acid (UDCA) treatment. [24] In a retrospective cohort of 58 PBC patients Chan et al confirmed the Nakanuma system as a prognostic factor for liver related events, while the Ludwig system was not. [27] It must be stated that, despite that PSC and PBC are both cholangiopathies, sharing biochemical, clinical and a some morphological features, considerable differences exist in both disease entities [15].…”
Section: Discussionmentioning
confidence: 98%
“…Kakuda et al [19] reported that the new PBC staging and grading system reflected liver dysfunction prior to specific treatment. In the present study, however, the expression of IgG and IgM did not appear to reflect clinicolaboratory features following intervention or specific treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Primary biliary cirrhosis (PBC) is characterized by nonsuppurative cholangitis and autoimmune-mediated destruction of the small or medium-sized bile ducts (8). Inflammation causes cholestasis and the liver develops cirrhosis (9). AIH is treated with immunosuppressive drugs, such as prednisolone or azathioprine (10,11), while PBC is treated with ursodeoxycholic acid (10).…”
Section: Introductionmentioning
confidence: 99%